HPCR practitioner's handbook on monitoring, reporting, and fact-finding : investigating international law violations / edited by Rob Grace, Claude Bruderlein. - Grace, Rob; Bruderlein, Claude (Cambridge University Press, 2017)
This book offers a portrait of the practice of monitoring, reporting, and fact-finding in the domain of human rights, international humanitarian law, and international criminal law. By analyzing the experiences of fifteen missions implemented over the course of the past decade, the book illuminates the key issues that these missions face and offers a roadmap for practitioners working on future missions. This book is the result of a five-year research study led by the Program on Humanitarian Policy and Conflict Research at Harvard University, Massachusetts. Based on extensive interviews conducted with fact-finding practitioners, this book consists of two parts. Part I offers a handbook that details methodological considerations for the design and implementation of fact-finding missions and commissions of inquiry. Part II - which consists of chapters written by scholars and practitioners - presents a more in-depth, scholarly examination of past fact-finding practices.